Non-competitive resource exploitation within mosquito shapes within-host malaria infectivity and virulence - G. Costa (Nature Portfolio, 2018)
The evolution of within-host malaria virulence has been studied, but the vector’s contribution isn’t well understood. Here, Costa et al. show that non-competitive parasitic resource exploitation within-vector, in particular lipid trafficking, restricts within-host infectivity and virulence of the parasite.